Phenomenology of Augmented Environments - Feyles, Martino (Aesthetica Preprint, 2020)
In this article I analyze the notion of augmented environment from a phenomenological point of view. Referring to the work of J. von Uexküll, I will define environment as the set of perceptual and operational possibilities that a living being projects into its surroundings. Recalling the distinction between world and environment proposed by Scheler and Heidegger, I will show that augmented perception implies a redefinition of the openness that defines the human world.